Structural assessment and seismic analysis of a 14th century masonry tower. (January 2020) - Micelli, Francesco; Cascardi, Alessio
Highlights: Geometrical survey of a 40 m height masonry bell tower by means of drone and images elaboration algorithm. Mechanical and chemical diagnostic of existing masonry with different non destructive tests. Seismic vulnerability assessment by means of modal, pushover and kinematic analyses. Strengthening design against overturning of masonry bell tower. Abstract: The masonry building Heritage embraces a large variety of structural typologies, including churches, bridges, arenas, theatres, portals, castles, temples, and towers. The structural behaviour of these constructions appears often complex to be understood due to the uncertainties related to the materials and internal geometry. In this paper, a complete study (i.e. from the data acquisition and elaboration to the vulnerability analysis and proposal for a non-invasive strengthening procedure) of a monumental bell tower building is reported. An extensive program of structural and geometrical surveys has been planned and performed. The main goal of the breakdown was to assess the stability and the seismic vulnerability of the bell tower. Moreover, an innovative use of the drone-based survey for the computation of the geometry of the structure is proposed, in order to significantly reduce the time-cost expenditure of the structural assessment, without any significant lack in the accuracy of the measurements. The resulting object, obtained from the drone-based digitalized survey, was inputted and set in a Finite Element Method (FEM) code for structural modelling. Moreover, a nonlinear kinematic analysis was performed to individuate the possible failure mechanisms. Finally, a non-invasive strengthening procedure, aiming to the improvement of the seismic capacity, is proposed.